2019
DOI: 10.1155/2019/2067196
|View full text |Cite
|
Sign up to set email alerts
|

A Pulse Signal Preprocessing Method Based on the Chauvenet Criterion

Abstract: Pulse signals are widely used to evaluate the status of the human cardiovascular, respiratory, and circulatory systems. In the process of being collected, the signals are usually interfered by some factors, such as the spike noise and the poor-sensor-contact noise, which have severely affected the accuracy of the subsequent detection models. In recent years, some methods have been applied to processing the above noisy signals, such as dynamic time warping, empirical mode decomposition, autocorrelation, and cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…The inappropriate data were removed in order to improve the robustness of PPK model, such as the data in case of poor subject compliance, mishandling of blood samples, inappropriately higher plasma concentrations or outliers, plasma concentrations lower than LLOQ, significant deviation of plasma concentration at the same time point based on Chauvenet Criterion (data will be removed if it meets the following requirement: |observation -mean| > W n *(standard deviation), where W n is the Chauvenet coefficient. Cumulative normal distribution probability of Chauvenet coefficient is 1-1/(4*n), where n is sample size (Ni et al, 2019)), or abnormal data revealed by diagnostic plot of PPK model, and the absolute value of weighted residual (|WRES|) > 5.…”
Section: Data Processingmentioning
confidence: 99%
“…The inappropriate data were removed in order to improve the robustness of PPK model, such as the data in case of poor subject compliance, mishandling of blood samples, inappropriately higher plasma concentrations or outliers, plasma concentrations lower than LLOQ, significant deviation of plasma concentration at the same time point based on Chauvenet Criterion (data will be removed if it meets the following requirement: |observation -mean| > W n *(standard deviation), where W n is the Chauvenet coefficient. Cumulative normal distribution probability of Chauvenet coefficient is 1-1/(4*n), where n is sample size (Ni et al, 2019)), or abnormal data revealed by diagnostic plot of PPK model, and the absolute value of weighted residual (|WRES|) > 5.…”
Section: Data Processingmentioning
confidence: 99%
“…Posteriormente, se aplicó el criterio de Chauvenet para eliminar los datos atípicos. Este criterio consiste en establecer un rango de probabilidad con todas las muestras de un conjunto de datos, también se especifica el valor medio, en el cual todos los datos fuera del rango se eliminan (Ni et al, 2019). Finalmente, se realizó una revisión exhaustiva de las cuentas para corroborar que los números expuestos tengan concordancia y verificar que existió el mismo número de empresas todos los años.…”
Section: Materiales Y Métodosunclassified
“…There have been several studies to identify suitable sensor and data collection devices with pressure sensors [4][5][6], piezoelectric sensors [4], optical sensors [5], and condenser microphones [2]. Signal preprocessing steps such as adaptive techniques [9,10], and filter-based methods [11,12] for noise removal, along with denoising and baseline wander removal, have been commonly utilized. Similar to other pulse signals, Nadi pulse segmenting [11,13] and outlier removal steps maximize the information extraction from the collected data.…”
Section: Introductionmentioning
confidence: 99%
“…A set of time and frequency data was analyzed with Independent Component Analysis(ICA), concluding it has the potential to be used as a classification method for diseases [8]. A two-dimensional feature extraction method that included the within-class information giving periodic and non-periodic features has been tested for diabetic diagnosis [9]. The authors have used a set of ratio-based features in both the time and frequency domains [18,19] for diabetes diagnosis as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation